Variation and hybridization in Sorghum almum Parodi - Gangstad, E.O. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
Variation and hybridization of Sorghum almum Parodi was observed in relation to prassic acid content, pollen fertility, seedling color, plant height, vizome expression, seed size, and seed separation. Topcross and polycross progeny tended to differ more in degree than in kind, but modest differences were observed. S. almum A 2781 and A 4836 were similar, while 54-2869 grew easily at 385 ms, and PI 190579 did not produce tall plants in the F progeny. The lateral rhizome of S. halepense was transferred to S. almum, but seed disarticulation was not evident in the progeny of S. almum polycrosses. The non-disjointed trait of S. almum was transferred to S. halepense, but the terminal rhizome was not observed in the progeny of S. halepense polycrosses. Efforts to improve the agronomic traits of S. almum Parodi were successful, and a new selection was obtained with low prussic acid potential, good winter persistence, high acceptability, and seed and forage yield.